CASEMIRO DOS REIS FILHO E A EDUCAÇÃO BRASILEIRA CASEMIRO DOS REIS FILHO AND THE BRAZILIAN EDUCATION - Dermeval Saviani (Educação & Sociedade, 2001)
O presente artigo procura traçar a trajetória do Prof. Casemiro dos Reis Filho a partir da origem de seus pais, em Portugal, passando pela sua escolarização no interior de São Paulo, sua formação em pedagogia na USP, o doutorado na PUC-SP, sua atuação destacada no magistério do ensino fundamental, médio e superior, na produção científica, na administração universitária e na divulgação de pesquisas educacionais, evidenciando sua relevante contribuição ao desenvolvimento da educação brasileira. The present paper seeks to trace the itinerary of Prof. Casemiro dos Reis Filho from his parent's origins, in Portugal, passing by his school years in inland São Paulo, his formation in pedagogy at USP and his doctor's degree at PUC-SP. It also stresses his highly praised activities as a teacher in the primary, secondary and higher education, not to mention his scientific production, university administration and eforts to spread educational research, thus highlighting his crucial contribution to develop Brazilian education.